Development of Nerve Fibre Diameter in Young Infants With Hirschsprung Disease. Issue 2 (February 2018) - Janssen Lok, Maarten; Rassouli-Kirchmeier, Roxana; Köster, Nils; Kusters, Benno; de Blaauw, Ivo
ABSTRACT: Objectives: Finding thickened nerve fibres is one of the key elements in the diagnosis of Hirschsprung disease (HD); however, its value at different ages remains uncertain. Nerve fibre diameters <40 μm can be observed in infants younger than 8 weeks, despite the presence of HD. The aim of this study was to identify a change in maximum nerve fibre diameter in HD patients, measured before and after 8 weeks of age. Methods: Nerve fibre diameter was retrospectively evaluated in tissue of 20 infants treated for definite HD. Rectal suction biopsies (RSBs) obtained within the first 8 weeks of life (T1) and resected bowel obtained during primary surgery at an average of 24.7 weeks (T2), were assessed. The 2 thickest nerve fibre diameter recordings at T1 and T2 were compared in each subject, to examine changes in nerve trunk diameter with increasing age. Results: In 13 cases (65%), nerve fibre diameters were ≥40 μm at T1 and T2. Six subjects (30%) had nerve trunk diameters <40 μm at T1; however, they experienced diameter increases to ≥40 μm by T2. Thus, at T2, 19 subjects (95%) had diameter recordings ≥40 μm. Nerve fibre diameter in the remaining case (5%) stayed consistent at <40 μm at T1 and T2, despite the presence of HD. Conclusions: After the first 8 weeks of life, nerve fibre measurements appear to be associated with HD. Measuring the 2 thickest nerve fibres can support typical HD diagnosis criteria beyond 8 weeks of age, but is not superior to histopathological confirmation of aganglionosis.